Oviduct-specific Glycoprotein is a Molecular Marker for Invasion in Endometrial Tumorigenesis Identified Using a Relevant Mouse Model - Wang, Hong (2009)
The light microscopic distinction between complex atypical hyperplasia (CAH) and invasive endometrioid carcinoma (UEC) on endometrial sampling is problematic and often has significant clinical implications. Using mouse models of endometrial tumorigenesis based on two of the most common molecular alterations found in primary human UEC we sought to characterize the transition from CAH to carcinoma to identify clinically useful biomarkers. We used the previously described Pten(+/-);Mlh1(-/-) mouse model. DNA was isolated from microdissected lesions (CAH and carcinoma) and analyzed for LOH and mutations of Pten and additional candidate genes. In order to identify novel candidate genes associated with invasion, global gene expression profiles were compared from uteri with extensive CAH and carcinoma. The majority of CAHs as well as carcinomas, arising in this model showed biallelic inactivation of Pten mediated through LOH or intragenic mutation of the wild-type allele suggesting that complete loss of Pten is insufficient for the development of carcinoma. The global gene expression studies detected increased expression of oviduct-specific glycoprotein (OGP) in carcinoma as compared to CAHs. This finding was validated using immunohistochemical staining in a collection of primary human UECs and CAHs. Our studies identify a molecular marker for invasive endometrial cancer that may have clinical significance, and highlight the usefulness of this mouse model in not only understanding the genetic underpinnings of endometrial carcinoma, but as a tool to develop clinically relevant biomarkers.